Valuing others in classical antiquity - Rosen, Ralph Mark; Sluiter, I. (Ineke) (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2010)
How does a discourse of 'valuing others' help to make a group a group? The fifth in a series exploring 'ancient values', this book investigates what value terms and evaluative concepts were used in Greece and Rome to articulate the idea that people 'belong together', as a family, a group, a polis, a community, or just as fellow human beings. Human communities thrive on prosocial behavior. In eighteen chapters, ranging from Greek tragedy to the Roman gladiators, and from house architecture to the concept of friendship, this book demonstrates how such behavior is anchored and promoted by culturally specific expressions of evaluative discourse. Valuing others in classical antiquity should be of interest to linguists, literary scholars, historians, and philosophers alike.